MENUMBUHKAN JIWA WIRAUSAHA KREATIF DALAM MASYARAKAT - Anam, Moh. (ABDI MASYARAKAT, 2025)
The purpose of this Community Service activity is to foster a creative entrepreneurial spirit within the Islamic boarding school community at the PPAI An-Nahdliyah Karangploso Malang Foundation. This activity is carried out through creativity training and mentoring, as well as the development of creative products that are beneficial to the community. The methods in implementing this Community Service activity include using lectures and group discussions so that this counseling is expected to increase knowledge, especially material regarding entrepreneurship, business concepts and product marketing strategies. The results of the activity show that participants can develop their creative and innovative potential, increase awareness of the importance of creativity in everyday life, and produce useful creative products. This activity is expected to be the first step in developing creativity and innovation among the Islamic boarding school community, as well as improving their quality of life and well-being.